2010
DOI: 10.1089/end.2010.0008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Percutaneous Nephrolithotomy and Tract Dilatation Methods on Renal Function: Assessment by Quantitative Single-Photon Emission Computed Tomography of Technetium-99m–Dimercaptosuccinic Acid Uptake by the Kidneys

Abstract: QSPECT of (99m)Tc-DMSA confirms that renal function is preserved or often improved after percutaneous stone removal, and nephrostomy tract dilatation methods have similar effects on renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Unsal et al measured the effects of PNL dilatation methods on renal function in adult patients using QSPECT and DMSA uptake by the kidneys. 15 Balloons, metal, and Amplatz dilators were compared, and no difference in renal uptake was found among the three groups pre-or postoperatively. New scarring was detected in 18% of patients, and 66% of these scars were reported to be at the site of the focal defect corresponding to the access site for tract formation during PNL.…”
Section: Discussionmentioning
confidence: 96%
“…Unsal et al measured the effects of PNL dilatation methods on renal function in adult patients using QSPECT and DMSA uptake by the kidneys. 15 Balloons, metal, and Amplatz dilators were compared, and no difference in renal uptake was found among the three groups pre-or postoperatively. New scarring was detected in 18% of patients, and 66% of these scars were reported to be at the site of the focal defect corresponding to the access site for tract formation during PNL.…”
Section: Discussionmentioning
confidence: 96%
“…The other parameters were not significantly affected in the early term. In another similar study, Ünsal et al [13] compared percutaneous dilatation methods (balloon, Amplatz, and Alken). They found that they did not affect the renal functions at the end.…”
Section: Discussionmentioning
confidence: 99%
“…[13,17,21,24] Regarding the damage to the treated kidney, PNL was again found to be unlikely to give rise to scarring in children. [23,[25][26][27][28] Dwaba et al [25] reported no scarring using dimercaptosuccinic acid (DMSA) renal scanning and stabilization or improved function with diethylene triamine pentaacetic acid (DTPA) renal scanning after PNL. To summarize, most studies demonstrate minimal scarring and insignificant loss of renal function after PNL.…”
Section: Discussionmentioning
confidence: 99%